Burnin' down the house : home in African American literature - Prince, Valerie Sweeney (Columbia University Press, 2005)
-- Cheryl A. Wall, Rutgers University.
Keywords: American fiction -- African American authors -- History and criticism.; Domestic fiction, American -- History and criticism.; African American families in literature.; African Americans -- Intellectual life.; African American women in literature.; African Americans in literature.; Dwellings in literature.; Families in literature.; Home in literature.; Roman américain -- Auteurs noirs américains -- Histoire et critique.; Familles noires américaines dans la littérature.; Noirs américains -- Vie intellectuelle.; Noirs américains dans la littérature.; Habitations dans la littérature.; Familles dans la littérature.; Foyer dans la littérature.; LITERARY CRITICISM -- American -- General.; LITERARY CRITICISM -- American -- African American.; African American families in literature; African American women in literature; African Americans in literature; African Americans -- Intellectual life; American fiction -- African American authors; Domestic fiction, American; Dwellings in literature; Families in literature; Home in literature; Criticism, interpretation, etc.